A Short Enantioselective Total Synthesis of (−)‐Englerin A1. Issue 20 (15th April 2013) - Zahel, Martin; Keßberg, Anton; Metz, Peter
<x xml:space="preserve">Abstract</x> Selective oxidations of dienone 2 as well as a ring‐closing metathesis to give the hydroazulene framework enabled the 12‐step preparation of title compound 1 from (−)‐photocitral A (3), which is in turn rapidly available from (−)‐isopulegol through dual catalysis.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>